What Can Reading Motivation Do for Improving Student’s Reading Comprehension? Implications for Reading Instruction in the School - Efriza, Dony; Deswarni, Dini; Sepyanda, Marsika (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study is a qualitative study which to know the problems of students’ reading motivation as an implication for reading instruction for improving reading comprehension. The instrument that had been used for this study is questionnaires and literature review was done to give solution for implication in the reading classroom based on theories. For 21 students in junior high school who have been distributed a questionnaire could be found that some students have some problems in reading efficacy and intrinsic motivation (reading work avoidance). Some solutions to solve students’ reading motivation are 1) Sociocultural environment is part of a solution in creating reading motivation in order peer influence happened on it. 2) By viewing locus of control, appropriate book and text determine the reading motivation of the students. 3) Furthermore, the students must be given the freedom to choose the kinds of text that they want to read. 4) reward and punishment can be applied on the reading class to invent students’ reading motivation 5) activating the school library can increase reading interest but must be accompanied by making several programs that support reading activities.